2016
DOI: 10.1111/cge.12897
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights on the genetics and epigenetics of endometriosis

Abstract: Endometriosis is a gynecologic disease affecting up to 10% of the women and a major cause of pain and infertility. It is characterized by the implantation of functional endometrial tissue at ectopic positions generally within the peritoneum. This complex disease has an important genetic component with a heritability estimated at around 50%. This review aims at providing recent insights into the genetic bases of endometriosis, and presents a detailed overview of evidence of epigenetic alterations specific to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(112 citation statements)
references
References 133 publications
(129 reference statements)
3
90
0
19
Order By: Relevance
“…In our study, no significant difference was observed between the pre‐ and post‐treatment implant volumes in the control group, similar to the studies reported in the literature . However, a significant difference was found between the pre‐ and post‐treatment implant volumes in the ALA group.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, no significant difference was observed between the pre‐ and post‐treatment implant volumes in the control group, similar to the studies reported in the literature . However, a significant difference was found between the pre‐ and post‐treatment implant volumes in the ALA group.…”
Section: Discussionsupporting
confidence: 91%
“…In addition it had the greatest sensitivity and specific of any single miRNA in surgically diagnosed patients. Indeed when combined with miR-451a and mIR-3613-5p a maximum AUC score 1.00 was achieved [15].…”
Section: Investigations In Gynecology Research and Womens Healthmentioning
confidence: 97%
“…As described earlier 13,14 12 age-matched adult female Lewis rats (RRID: RGD_737932) obtained from Harlan Laboratories GmbH (Venray, The Netherlands), were subjected to ovariectomy (OVX) to reduce the levels of endogenous estrogen. Fourteen days after surgery the OVX animals were randomized to two treatment cohorts (n = 6).…”
Section: Animals and Dietmentioning
confidence: 99%